2016
DOI: 10.1097/01.asw.0000480359.58866.e9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chicken-Egg Membrane as a Dressing for Wound Healing

Abstract: Chicken-egg membrane dressing significantly improves healing of cutaneous wounds in the early stages of wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…We have previously demonstrated that this material holds promising anti-inflammatory effects [ 16 ] and activating of epithelization and fibroblast in this study could indicate a broad specificity in treatment. Also, Guarderas et al showed that chicken egg-membrane dressing significantly improved healing of cutaneous wounds in early stages of wound healing in Spraque-Dawley rats [ 1 ]. Cutaneous wound repair and chronical wounds express specific MMP-profiles [ 57 , 58 ], and further studies on effects on MMP-activity in different wound models would be necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that this material holds promising anti-inflammatory effects [ 16 ] and activating of epithelization and fibroblast in this study could indicate a broad specificity in treatment. Also, Guarderas et al showed that chicken egg-membrane dressing significantly improved healing of cutaneous wounds in early stages of wound healing in Spraque-Dawley rats [ 1 ]. Cutaneous wound repair and chronical wounds express specific MMP-profiles [ 57 , 58 ], and further studies on effects on MMP-activity in different wound models would be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as an alternative natural bandage on burned and cut skin injuries for more than four hundred years in Asian countries. Recently, a study demonstrated an ESM-positive effect in a rat skin wound model, by decreasing wound closure time [ 1 ]. ESM is a highly fibrous material that is readily available as a remnant of the chicken egg processing (breaking) industry, and therefore shows potential as a low-cost ingredient for wound treatment products.…”
Section: Introductionmentioning
confidence: 99%
“…Providing a scaffold for the fibroblast migration and reducing the lag phase for wound healing [ 119 ]…”
Section: Figurementioning
confidence: 99%
“…It has been used as an alternative natural bandage on burned and cut skin injuries for >400 years in Asian countries. Recently, a study has demonstrated its positive effect in a rat wound model, by decreasing wound closure time 2. So far, mechanisms of how ESM actually works on wound healing, or the bioactive components involved in this process, are far from understood.…”
Section: Introductionmentioning
confidence: 99%